Intergenerational dialogue of cohabiting adult children and their parents – the socio-economic perspective - Wieteska, Magda (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
In this article I present the reasons for postponing adulthood included in the conclusions from studies of young adults residing with their parents.
Keywords: autonomy; maturity; adulthood; crisis intervention centers; home; work; family